The Use Of E-Flash Card Assisted By Heyzine With Problem Based Learning Method To Improve English Vocabulary Of Third Grade Students At Sd N 5 Besakih - Andriani, Ni Luh Eka (CV. Jendela Edukasi Indonesia, 2025)
Vocabulary mastery is very importance in learning English especially for elementary school children. This studi aims to improve students English vocabulary especially about fruits with E-Flash Card assisted by Heyzine with Problem Based Learning method. The data collection instruments included tests (pretest, post-test I, and posttest II), observation, and documentation. Data analysis techniques were carried out quantitatively and qualitatively with learning achievement indicators of at least 80%. The results showed an increase in the average student score from 50.3 (pretest), to 60.30 (post-test I), and 71.53 (post-test II). Classical completeness also increased from 30.77% (pretest), to 76,92% (post-test I), and icreased again to 92.30% (post-test II). This increase shows that the Use Of E-Flash Card assisted by Heyzine with Problem Based Learning Method can improve students vocabulary and is effective to be applied to in teaching and learning activities.